Evaluation of adjuvant therapy for T1-2N1miM0 breast cancer without further axillary lymph node dissection - Li, Baiyu; Liu, Jianbo; Wu, Guangyin; Zhu, Qingyao; Cang, Shundong (Frontiers in Surgery, 2023)
Background: For breast cancer (BC)with sentinel lymph node micrometastases (SLNMs), there are limited data to guide selection of postoperative adjuvant therapy. This study aimed to identify target populations who might benefit most from adjuvant therapy and examine prognostic factors among patients with T1-2N1miM0 BC with one or two SLNMs who underwent sentinel lymph node biopsy (SLNB) alone. Methods: There were 7423 patients diagnosed with T1-2N1miM0 BC between 2010 and 2015, and patients with one or two SLNMs were extracted from the Surveillance, Epidemiology, and End Results database. All the patients underwent SLNB alone without further axillary lymph node dissection, and they were stratified according to adjuvant therapy. Statistical significance of categorical variables was analyzed using the chi-square test. Univariable and multivariable Cox were used to analyze characteristics predictive of Breast-cancer-specific survival and overall survival (OS) . Kaplan–Meier methods with the log-rank test was analyzed to compare survival difference between the different treatments. Results: Adjuvant chemotherapy and radiotherapy improved 5-year OS rates. Multivariate analysis revealed that age ≥70 years, high grade, T2 stage, triple-negative subtype, and absence of radiotherapy were poor prognostic factors for OS. Patients who received breast-conserving surgery, and those with invasive ductal carcinoma, luminal A, luminal B or basal-like subtype, and T1c or T2 stage benefited from adjuvant radiotherapy. Patients who received breast-conserving surgery, and those with invasive ductal carcinoma, luminal A subtype, and T1b, T1c or T2 stage benefited from adjuvant chemotherapy. Conclusion: Our findings provide clinical evaluation of treatment choice after surgery, which may help clinicians make individualized clinical decisions.